2014
DOI: 10.1590/s0103-84782014000100011
|View full text |Cite
|
Sign up to set email alerts
|

Capacidade produtiva e progresso genético de pinhão-manso

Abstract: RESUMO O objetivo do presente estudo foi estimar parâmetros genéticos e avaliar o progresso genético dos principais componentes da produção de grãos do pinhão-manso. Para isso

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
3
1
1
Order By: Relevance
“…For its part, the number of fruits per truss showed greater potential for selection than the number of trusses per plant, in contrast with that observed by Borges (2012). This author did not observe genetic variability for number of fruits per trusses in a population structured by origin.…”
Section: Resultscontrasting
confidence: 64%
“…For its part, the number of fruits per truss showed greater potential for selection than the number of trusses per plant, in contrast with that observed by Borges (2012). This author did not observe genetic variability for number of fruits per trusses in a population structured by origin.…”
Section: Resultscontrasting
confidence: 64%
“…This suggests that selection for one trait promotes indirect selection gains for the other. Plant height was also found to be suitable for the early selection of Jatropha curcas plants (Borges et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…This method has been applied for several species such as eucalyptus (Silva et al, 2013), cotton (Farias et al, 2016), rubber tree , and strawberry (Costa et al, 2015). However, few types of research have reported the use of this method in Jatropha breeding (Borges et al, 2014). Therefore, the objectives of this study were to estimate genetic parameters based on Jatropha full-sib families performance and to select superior genotypes for grain yield, adaptability, and stability simultaneously.…”
Section: Introductionmentioning
confidence: 99%